Mental health services for people with learning disabilities and other related disorders in supported living in Iceland - Íris Björk Indriðadóttir 1996- (2021)
In the recent years it has been acknowledged that individuals with a learning disability (LD) are likely to display emotional troubles similar to people without an LD and studies show that people with a learning disability (PWLD) may be at an increased risk for developing a mental illness. In some countries psychologists and psychiatrists specialise in mental health problems of PWLD but this is not the case in all countries and general psychiatrists and other professionals may care for PWLD with mental disorders without having special knowledge of their problems. The lack of professionals trained to treat PWLD with mental health problems contributes to limited access to mental health services and low quality of care. For the current study, two hypotheses were tested: 1) PWLD living in Iceland do not receive adequate mental health care and 2) a large proportion of PWLD with supported living in Iceland use psychotropic medication. A questionnaire was sent to managers of all supported living services for PWLD in an attempt to explore the use, need and accessibility of mental health services within the group. Among the responses for 562 PWLD, 37.2% were diagnosed with a mental disorder, 66.0% did not have access to mental health services, and 58.2% were on psychotropic medication. Landssamtökin Þroskahjálp Átak, félag fólks með þroskahömlun Geðsvið Landspítalans Heilsugæsla Höfuðborgarsvæðisins